(3CQLhRI aj JYHjQ GdQDjG Ydi UaI Ndb GdEfSGfs - (3CHh GdMSf Ydj Hf GdScf GdeYGaQi GdeaSQs ((3GHi GdaVd eMeO GdCYQL s)
(3ChdgG (B:s
(3GdMeO ddg Ydi JbOjQg EP CMSf GdGfSGf ai JUhjQg s
(3BNQgG (B:s
(3Ydi GdgOi hGdQTO hGdJhajb hbhdfG ddMb HGdJMbjb s
(3PcQ ajgG JaSjQ dCYVGA GdGfSGf hGfaYGdGJg GdeNJdaI Mjf Gdfhes
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3fXe s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3JYHjQ GdQDjGs